Effectiveness of Drying, Roasting and Preservation on Antioxidant of Dried Roasted Sunflower (Helianthus Annuus) Seed - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Antioxidants are considered important nutraceuticals on account of many health benefits. Due to the high antioxidant activity, Helianthus annuus seeds might be considered in the management and prevention of degenerative diseases associated with free radical damage. It is the rich source of vitamins specially vitamin E. Drying and roasting are the most important processes giving neccessary alterations to the product. Roasting can enhance flavour through caramelization on the surface of the food. There was no any research mentioned to varify the change of antioxidant (tocopherol) during heat pump drying as well as storage. So the objective of the present study was to identify the effect of temperature in heat pump drying, roasting condition, packaging and storage to antioxidant (tocopherol) in the dried Sunflower (Helianthus annuus) seed. Results demonstrated that drying temperature (40 oC), roasting (145 oC in 5 min), vaccum packing in polyethylen (PA) bag and keeping in 4 oC were recommended to maintain the tocopherol, total phenolic and antioxidant activity in the final products for 12 months. The effect of drying, roasting temperature and time were clearly demonstrated to produced dried roasted sunflower seed.Keywords: Sunflower, Drying, Roasting, Antioxidant, Tocopherol, Vaccum.